Finding your lane: experiences and beyond for adults learning to swim - Shawn Wilson; Alison Moira Miller; Destiny Casson; William D. Ramos (BMC, 2023)
Abstract The purpose of this study was to examine experiences and impacts from participating in an adult swim instruction program. We conducted 20 semi-structured interviews with adults aged 18 + who had participated in an adult learn to swim program. Participants were interviewed through a virtual platform using a semi-structured protocol. Data were coded individually by each member of the research team for emerging thematic outcomes with final consensus among all those involved in the analysis. Participants expressed adult learn to swim programs had an effect in three areas: (a) life affordance, (b) emotional affect, and (c) interpersonal relationships. Public health experts and aquatics leaders should consider targeting programs aimed at teaching adults to learn how to swim, especially to marginalized individuals and those who did not grow up in the United States. The authors highlight how these programs can create life affordances well beyond lap swimming and even water safety.